Interactions between bats and floral resources in a premontane forest, Valle del Cauca, Colombia - Mora-Beltrán, Catherine; López-Arévalo, Hugo Fernando (THERYA, 2018)
The study of interaction networks between species is a subject that has drawn increasing attention in recent decades, especially in investigations involving relationships between plants and pollinators or seed dispersers. In the Neotropics, bats of the subfamily Glossophaginae show morphological modifications for a specialized diet consisting of nectar and pollen, but opportunistic species belonging to other subfamilies that consume floral resources (nectar and pollen) have also been identified. This study describes for the first time the interactions between nectarivorous bats in the Andean region of Colombia from the identification of pollen associated with the bat species inhabiting the protected area â€œReserva Forestal Bosque de Yotoco (RFBY)â€. Bats were captured with mist nets; a pollen sample was collected from each specimen by contact with glycerin gelatin, and pollen samples were mounted on slides. In addition, plant material of the blooming species that displayed the syndrome of chiropterophyly was collected to build a reference pollen collection. For the analysis, we used Levinâ€™s standardized niche breadth (BA), the relative frequency of resources (Fi), and the Resource Importance Value Index (RIVI). The interaction network was built and the NODF nesting algorithm was calculated to establish the degree of coupling within the network. In 44 loads of contact pollen for six species, three belonging to the subfamily Glossophaginae (Anoura caudifer, Glossophaga soricina and Choeroniscus godmani), we identified six palynomorphs from 7,971 pollen grains. The highest RIVI values correspond to three species of the genus Inga. The Levinâ€™s standardized niche breadth (BA) highlights Anoura caudifer and Glossophaga soricina as generalist species that take advantage of the availability of floral resources for consumption (Tables 2, 3). The interaction network reveals a high nesting degree according to the value of the NODF algorithm of 86.67 (Figure 3). With four bat species, the RFBY has a high diversity of nectarivorous species relative to other localities across the Andean region of Colombia, despite the study area being a fragmented landscape; hence, this area is of critical importance for the local bat species, as it fulfills their food requirements. The bat species using the largest amount of resources in the community is Anoura caudifer; this finding differs from the results of other studies, where the genus Glossophaga has been reported as the dominant taxon in terms of resource use. Plants of the genus Inga and O. pyramidale are key resources for the nectarivorous bat species recorded, and this is probably also the case for other animals in the area; therefore, the inclusion of these species in the active restoration process will likely promote the establishment of a larger number of bats.